SAT0634-HPR Development and Reliability of Turkish Version of the Short Form-Joint Protection Behavior Assessment (JPBA-S). (9th June 2015) - Tonga, E.; Uysal, S.A.; Karayazgan, S.; Hayran, M.
Abstract : Background: Joint Protection Behavior Assessment was developed to evaluate the patient's use of behaviors in daily activities with hand using in patients with rheumatoid arthritis. A short version of the JPBA (JPBA-S) consisting of 10 tasks for the activity of preparing instant coffee has been found to be reliable compare with the full-length JPBA. Objectives: To adapt the original JPBA-S to a Turkish version (TUR-JPBA-S) and to develop assessment manual and to investigate the reliability of assessment in patients with RA. Methods: 15 participants with RA were videotaped while they were doing tasks in original version for manual development and face validity (phase 1). The video recordings were analyzed by two therapists. TUR-JPBA-S was developed with the consensus of four therapists who were working on occupational therapy. 22 participants with RA and 21 healthy people were videotaped while doing TUR-JPBA-S for the second part of the study (phase 2). Two raters were analyzed the records and gave a rate to strictly follow the manual (inter-reliability). One rater were re-analyzed the recordings at different time point (intra-rater reliability). Participants with RA were re-recorded after three to four weeks period. One rater analyzed the re-records (test-retest reliability). The evaluators' composite results were compared between and within raters using the kappa coefficient and ICC's for categorical scoring respectively. Results: There were some differences in TUR-JPBA-S. For example; (i) therapists decided with consensus to videotape the participants while they were making tea in Turkish style teapot with using cattle for heating up the water; (ii) the task "holding milk" were changed as "carrying tray". Internal consistency (Cronbach α value) was found to be high (0.89) for participants with RA. There was a significant difference in JPBA scores between patients with RA and healthy participants (p<0, 001). Our results demonstrated excellent intra-rater (ICC: 0.99, SEM: 1.2) inter-rater (ICC: 0.99, SEM: 1.7) reliability. Also excellent test retest reliability was found (ICC2:1, 0.96). There was a 100% agreement in 5 tasks in intra-rater agreement while there was 100% agreement in 4 tasks in inter-rater agreement. Conclusions: The TUR-JPBA-S provides valid and reliable instrument for assessing JP behavior of patients with RA in Turkey. References: Hammond A and Lincoln N. Development of the Joint Protection Behavior Assessment. Arthritis Care Res. 1999 Jun;12(3):200-7. Niedermann et. al. Development and validation of a German version of the joint protection behavior assessment in patients with rheumatoid arthritis. Arthritis Rheum. 2007 Mar 15;57(2):249-55 Niedermann et. al. Effectiveness of individual resource-oriented joint protection education in people with rheumatoid arthritis. A randomized controlled trial Patient Education and Counseling 82 (2011) 42–48. Acknowledgements: We want to thank to Prof. Alison Hammond to give permission for using assessment and support our research. Disclosure of Interest: None declared